2015
DOI: 10.2174/1570161112666141002121429
|View full text |Cite
|
Sign up to set email alerts
|

Coffee: A Selected Overview of Beneficial or Harmful Effects on the Cardiovascular System?

Abstract: With a history that began in 800 A.D., coffee is the most popular drink known and as a result, the issues regarding its physiologic effects deserve attention. Maintaining alertness is a wellknown benefit and in addition, the cardiovascular (CV) effects of the active compounds, which include polyphenols and caffeine, must be considered. Genetics are relevant and where slow caffeine metabolism is inherent, the risk of nonfatal myocardial (MI) has been shown to be increased. Overall risk for coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Unfortunately, the items in the FFQs did not distinguish between filtered versus unfiltered coffee or salted versus unsalted nuts, which are important distinctions in the new dietary guidelines. This may have led to an underestimation of the magnitude of the associations for the outcomes that have been particularly associated with coffee and salt consumption in the previous literature such as cardiovascular disease, type 2 diabetes and dementia [ 36 38 ]. For some food groups, no quantitative cut-offs were provided in the dietary guidelines, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the items in the FFQs did not distinguish between filtered versus unfiltered coffee or salted versus unsalted nuts, which are important distinctions in the new dietary guidelines. This may have led to an underestimation of the magnitude of the associations for the outcomes that have been particularly associated with coffee and salt consumption in the previous literature such as cardiovascular disease, type 2 diabetes and dementia [ 36 38 ]. For some food groups, no quantitative cut-offs were provided in the dietary guidelines, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although the explicit mechanisms of the association of coffee consumption and all‐cause mortality remain unclear, several mechanisms have been proposed. Caffeine contained in the product coffee affects the cardiovascular system and central nervous system . Some studies found moderate caffeine consumption to be associated with a reduced risk of all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported caffeine to exhibit protective ability against cellular damage (Krisko et al, 2005), thus effective in preventing LDL oxidation (Lee, 2000), reduces MDA levels, augments the activities of hepatic catalase and superoxide dismutase (SOD) (Mukhopadhyay et al, 2003) and possess anti-inflammatory effect (Whayne, 2015;Chen et al,2010;Lvet al,2010). Others suggests that caffeine isable to induce certain forms of oxidativedamage by increasing lipopolysaccharide(LP) (Dianzani et al, 1991;Al Moutaery et al, 2003), increased MDA levelsin the livers of rats (Karas et al, 2001), reduced Na+/K+-ATPase activities and increased NO levels by raising the endothelial NOS expression in the kidneys (Umemura et al, 2006;Lee et al, 2002).…”
Section: Issn: 2320-5407mentioning
confidence: 99%